2021
DOI: 10.15761/jts.1000398
|View full text |Cite
|
Sign up to set email alerts
|

Review of individual placement and support (IPS) studies and results on health status of people with long-term mental disorder and competitive employment

Abstract: Ordinary employment, from the vulnerability-stress model, is believed to trigger relapses in people with long-term mental disorders when subjected to demanding work environments. To test the accuracy of this hypothesis, different databases between 1998 and 2019 (May) were consulted, using various key words. Randomized Clinical Trials (RCTs) that analyzed non-vocational outcomes related to symptomatology and hospitalizations in the Individual Placement and Support (IPS) strategy with severe mental disorders wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(177 reference statements)
0
1
0
Order By: Relevance
“…Conducting a rapid search method for a competitive job, no exclusion criteria, a focus on client preference, targeted job development, integration of employment and mental health treatment services, personalized counselling, and long-term support are the core principles of this service [3]. Numerous studies have demonstrated the effectiveness of IPS in promoting employment for people with severe mental illness [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting a rapid search method for a competitive job, no exclusion criteria, a focus on client preference, targeted job development, integration of employment and mental health treatment services, personalized counselling, and long-term support are the core principles of this service [3]. Numerous studies have demonstrated the effectiveness of IPS in promoting employment for people with severe mental illness [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%